Catch Composition of Fix-Liftnet Based-on the Light Color Combination in Pangkep Waters - Saragih, Paramita; Kurnia, Muhammad; Amir, Faisal (Torani Journal of Fisheries and Marine Science, 2021)
This study aims to describe the composition of the species and the frequency of occurrence of fix-liftnet based on the combination of white-yellow-blue and white-yellow Light Emitting Diode (LED). The research was carried out in July – October 2020, by following the operation of capturing 1 unit of fix-liftnet with 442 watts of light power each. Data collection includes the type and number of catches based on trips and grouped into main, by-catch and discarded catches. The results showed that the composition of the type of catch consisted of 26 species dominated by common ponyfish, Indonesian oil-sardine, squid, anchovies, crabs, yellow snakehead and fringesscale sardinella. The total catch of the combination of white-yellow-blue lights was 359.8 kg with main catch 74.4%, by-catch 19.8% and waste 5.9%. While the white-yellow color combination is 343.8 kg with 75.8% main catch, 15.5% by-catch and 8.3% waste. Fish species with 100% occurrence frequency were common ponyfish (Leiognathus equulus), flower crab (Portunus pelagicus), squid (Loligo sp), Indonesian oil-sardine (Sardinella gibbosa), and smooth pufferfish (Lagocephalus sceleratus).